(N|LEMENTY MATEMATI^ESKOJ FIZIKI (B:s (NsREDA IZ NEWZAIMODEJSTWU@]IH ^ASTIC (B/s - (NzELXDOWI^(B, (NqKOW bORISOWI^s; (NmY[KIS(B, (NaNATOLIJ dMITRIEWI^s ((NmOSKWA (B:s (NnAUKA(B. (NgL(B. (NRED(B. (NFIZ(B.-(NMAT(B. (NLIT(B.,s, 1973)
(NpREDM(B. (NUKAZ(B.: (NS(B. 347-351s
Keywords: (NmATEMATI^ESKAQ FIZIKAs